Correlation between Physico-Chemical Properties and Engineering Properties of Soil Samples from Pinousuk Gravel Deposit of Mesilou, Kundasang, Sabah Mesilou, Kundasang, Sabah - Hennie Fitria Wulandary Soehady Erfen; Baba Musta; Darmesah Gabda; Junaidi Asis (2020)
Ten soil samples from Pinousuk Gravel unit were collected for physico-chemical and engineering properties investigation. Pinousuk Gravel originated from different parent rocks namely ultrabasic, granodiorite, sandstones, and shale from sedimentary rock formations. The correlation between physicochemical and engineering properties were analyzed using Spearman’s correlation. The result of analysis shows strong relationship (range from .59 to .83) between moisture content (V1) and clay percentage (V7) on the compressive strength (V13) of soil. This is due to the increasing of the liquid limit (V9) and soil plasticity (V11) which decrease the strength of soil.